COMPETITIVENESS OF TOURISM DESTINATIONS: A MIXED-METHOD BIBLIOMETRIC APPROACH - John, Ashna; Firoz C, Mohammed (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
Even after almost three decades of introduction of competitiveness into tourism sector, there is still a rising trend in literature on Tourism Destination Competitiveness (TDC). Though there are a few systematic and traditional reviews in the domain, there has been no study of the bibliometric variables. This study utilises Web of Science (WoS) database to conduct a bibliometric analysis of 166 documents on TDC, revealing the domain’s research trend in terms of authors, sources, and publications. The science mapping tool bibliometrix R-package is used to analyse the trend of scientific publications in the area, untapped knowledge, possible future trends, and implications. The analysis is undertaken on three levels: source, author, and document, as well as three types of knowledge structures: conceptual, intellectual, and social. The bibliometric data analysis consists of a descriptive analysis of the bibliographic data frame and network analyses and its graphical visualization. As per the analysis, competitiveness of natural/cultural destinations is rarely assessed in the global scenario. Maximum number of studies in the domain are carried out in European countries. The findings can guide researchers to focus on less developed themes/areas.